2010
DOI: 10.1103/physrevb.81.115458
|View full text |Cite
|
Sign up to set email alerts
|

Electrical rectification by selective wave-function coupling in small Ag clusters onSi(111)(7×7)

Abstract: A cluster consisting of as few as three Ag atoms deposited on Si͑111͒-͑7 ϫ 7͒ surface was found to behave as a strong electric rectifier, with a rectification ratio as large as ϳ150. Based on first-principles calculations, we found that the wave functions of electronic states at different energies spread out from the surface to different distances. We demonstrated by theoretical simulations and experiments that the observed rectification is a result of coupling the scanning tunneling microscope tip with select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…This distance is only slightly larger than the height of the Si ad-atoms above Si-1a (∼1.6Å 27 ), which implies that the Ag atoms in the wetting layer are located laterally between the Si ad-atoms within the Si ad-atom layer. This location of the Ag is consistent with low-temperature STM studies which have suggested that Ag adsorbs at high coordination sites between the Si ad-atoms in the case when only one or two Ag atoms occupy a HUC 34,35 , although, in those studies the height was not determined.…”
Section: Discussionsupporting
confidence: 87%
“…This distance is only slightly larger than the height of the Si ad-atoms above Si-1a (∼1.6Å 27 ), which implies that the Ag atoms in the wetting layer are located laterally between the Si ad-atoms within the Si ad-atom layer. This location of the Ag is consistent with low-temperature STM studies which have suggested that Ag adsorbs at high coordination sites between the Si ad-atoms in the case when only one or two Ag atoms occupy a HUC 34,35 , although, in those studies the height was not determined.…”
Section: Discussionsupporting
confidence: 87%
“…Other positions do not correspond to the other energy minima. The location of the Ag trimers observed by Hu et al [26] makes this difference plausible (see Ref. [26]).…”
Section: Structural Modelsmentioning
confidence: 95%
“…The location of the Ag trimers observed by Hu al. [26] makes this difference plausible (see Ref. [26]).…”
Section: Structural Modelsmentioning
confidence: 99%
“…All the clusters exhibit certain degrees of rectification behavior, 31 and, as a consequence, an onset sample bias needs to be applied, above which reasonable current responses can be obtained. For clusters from Ag 3 to Ag 26 , the onset sample bias ranges from +1 V to +2 V. To ensure that all the clusters studied would appear as protrusions, the STM images are taken at a sample bias of +2 V. The influence of the STM tip to the cluster dynamical movements is also examined by varying the sample bias and the tunneling current applied in the measurements, and we conclude that using a sample bias of 2 V and a tunneling current smaller than 100 pA will only bring negligible influence to the movement rate of the clusters.…”
Section: Experiments and Theoretical Calculationmentioning
confidence: 99%
“…[18][19][20][21] For example, Ag or Au clusters on oxide surfaces were found to exhibit high catalytic activity and selectivity for commercially important reactions such as propylene epoxidation 22,23 and CO oxidation. 24,25 In particular, variations in the clusters' configurations 22 and adsorption sites [24][25][26][27] can often influence their catalytic performance, in addition to the demonstrated changes in physical [28][29][30][31] or chemical 22,23 properties by adding/removing just one single atom to/from such clusters. The critical role played by the heterogeneous sites is exemplified by Au clusters on TiO 2 , with the Ti atoms neighboring Au becoming highly catalytic.…”
Section: Introductionmentioning
confidence: 99%